Implikasi Fiqh Ibadah dalam Kehidupan Sehari-Hari - Setiawan, Risky; Andrialam, Andesta Maharani Putri; Safroni, Ahmad Fajri; Andina, Putri; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe how the understanding of fiqh of worship influences the attitudes and behaviors of Muslims in their daily lives. Fiqh of worship not only discusses the formal procedures of religious rituals but also contains values that are reflected in daily habits, social interactions, and individual mindsets. Using a qualitative approach and data collection techniques through literature review and interviews with several informants, this research reveals that values such as discipline, cleanliness, social concern, and inner peace can grow through the deep understanding and practice of worship. The findings indicate that fiqh of worship is not merely a set of ritual procedures but also contributes significantly to shaping the character and quality of a Muslim’s life.